Global Constitutionalism in Crisis: A Review of Power Conflicts, Populism, and Federalism Challenges - Wilson Lambertus Situmorang (Journal of Social and Humanities, 2026)
This review examines the contemporary crisis of global constitutionalism by focusing on three interrelated pressures: conflicts over power, populist challenges to constitutional institutions, and the weakening of federal or quasi-federal balances between central and subnational governments. It argues that constitutionalism in the twenty-first century can no longer be understood merely as the formal existence of a written constitution. Rather, it must be evaluated through the actual operation of constitutional limits, the independence of courts and oversight bodies, the integrity of amendment procedures, and the capacity of federal arrangements to constrain central domination. Drawing on comparative constitutional and political science scholarship, the article shows that power conflicts may generate democratic constitutional reform when managed through lawful procedures, yet they may also produce abusive amendment, executive aggrandizement, and constitutional manipulation when institutional safeguards are weak. Populism intensifies these risks by presenting a unitary claim to represent “the people,” thereby delegitimizing courts, legislatures, media, and oversight agencies as obstacles to majority will. Meanwhile, crises of federalism often emerge when fiscal, administrative, or security instruments enable the center to narrow constitutionally guaranteed regional autonomy. The review concludes that constitutional resilience requires stronger judicial independence, transparent amendment rules, robust legislative oversight, civic constitutional culture, and intergovernmental mechanisms that prevent both executive and central-government overreach.